In vitro effects of recombinant adenovirus-mediated bone morphogenetic protein 2/vascular endothelial growth factor 165 on osteogenic differentiation of bone marrow mesenchymal stem cells. (2nd January 2017) - Han, Tian-Yu; Liu, Xin-Wei; Liang, Na; Liu, Yun-En; Zhang, Yu-Biao; Zhou, Da-Peng; Xiang, Liang-Bi
Abstract: Mouse bone marrow mesenchymal stem cells C3H10T1/2 were divided into Ad-BMP2 (bone morphogenetic protein 2) group, Ad-VEGF165 (vascular endothelial growth factor 165) group, Ad-VEGF165 + Ad-BMP2 group, empty adenovirus group and control group. BMP2 and VEGF165 were highly co-expressed in Ad-VEGF165 + Ad-BMP2 group. Ad-BMP2 and Ad-VEGF165 + Ad-BMP2 groups, especially the latter ( P  < 0.05), had significantly higher expression levels of osteocalcin, osteoprotegerin, and osteopontin mRNA and OPN protein ( P  < 0.05). Ad-VEGF165 + Ad-BMP2 group had highest alkaline phosphatase (ALP) activity, strongest ALP staining and most calcium salt deposits ( P  < 0.05). Combining VEGF165 obviously enhanced the inducing effects of BMP2 on osteogenic differentiation capacity of C3H10T1/2 cells.